Factors associated with loss to follow-up before and after treatment initiation among patients with tuberculosis: A 5-year observation in China - Jiang, Youli; Chen, Jingfang; Ying, Meng; Liu, Linlin; Li, Min; Lu, Shuihua; Li, Zhihuan; Zhang, Peize; Xie, Qingyao; Liu, Xuhui; Lu, Hongzhou (Frontiers in Medicine, 2023)
Background Loss to follow-up (LTFU) is a significant barrier to the completion of anti-tuberculosis (TB) treatment and a major predictor of TB-associated deaths. Currently, research on LTFU-related factors in China is both scarce and inconsistent. Methods We collected information from the TB observation database of the National Clinical Research Center for Infectious Diseases. The data of all patients who were documented as LTFU were assessed retrospectively and compared with those of patients who were not LTFU. Descriptive epidemiology and multivariable logistic regression analyses were conducted to identify the factors associated with LTFU. Results A total of 24,265 TB patients were included in the analysis. Of them, 3,046 were categorized as LTFU, including 678 who were lost before treatment initiation and 2,368 who were lost afterwards. The previous history of TB was independently associated with LTFU before treatment initiation. Having medical insurance, chronic hepatitis or cirrhosis, and providing an alternative contact were independent predictive factors for LTFU after treatment initiation. Conclusion Loss to follow-up is frequent in the management of patients with TB and can be predicted using patients’ treatment history, clinical characteristics, and socioeconomic factors. Our research illustrates the importance of early assessment and intervention after diagnosis. Targeted measures can improve patient engagement and ultimately treatment adherence, leading to better health outcomes and disease control.